2022
DOI: 10.1002/jmri.28535
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Interstitial Fibrosis in Chronic Kidney Disease by Diffusion‐Relaxation Correlation Spectrum MR Imaging: A Preliminary Study

Abstract: BackgroundRenal interstitial fibrosis is one of the most common pathways in the progression of chronic kidney disease (CKD). Noninvasive evaluation of interstitial fibrosis would help monitoring CKD progression and prognosis prediction.PurposeTo evaluate the severity of renal interstitial fibrosis by diffusion‐relaxation correlation spectrum imaging (DR‐CSI).Study TypeProspective.SubjectsForty patients with CKD and 10 healthy controls (average age 49.2 ± 14.8 years, 18 females).Field Strength/Sequence3‐T, DR‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The spectral characteristics of normal cortex were found to be consistent with those observed in a previous study focused on renal interstitial fibrosis. 27 The results of this study suggested that sub-regions B and D were associated with the histological grades of ccRCC. The utility of these sub-regions can be reasonably explained.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…The spectral characteristics of normal cortex were found to be consistent with those observed in a previous study focused on renal interstitial fibrosis. 27 The results of this study suggested that sub-regions B and D were associated with the histological grades of ccRCC. The utility of these sub-regions can be reasonably explained.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to the ex vivo studies that utilized MDCM methods to determine the specific spectral peaks of intra-voxel tissue components based on prior knowledge of tissue microenvironments, 24,25 T2, ADC, and DR-CSI face challenges in providing biological interpretation for in vivo studies due to their lack of specificity in tissue microenvironments. 18,19,27 This low specificity is not unique to MDCM methods but is a challenge for all MRI methods. The dynamic changes of in vivo tissue microenvironments in tumor, e.g., the intracellular or extracellular water, barriers or membranes, or microvascular structures would interfere with each other, making it difficult for MRI methods to measure and resolve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations